Kajian Pengelolaan Limbah Bahan Berbahaya Dan Beracun (Lb3) Padat Yang Dihasilkan Puskesmas Di Kabupaten Lebong - Rani, Eka; Utama, Satria Putra; Uker, Damres; Martono, Agus; Romeida, Atra (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2024)
Health centers in Lebong Regency have the potential to produce solid waste of the B3 type, so it is necessary to pay attention to its management starting from the source, generation, storage, collection, and processing of solid B3 waste so as not to have an impact on environmental pollution. Therefore, this study aims to determine the implementation of solid B3 waste management and waste generation and solid B3 waste management facilities of health centers in Lebong Regency. The research method used is a qualitative approach with quantitative data and a descriptive case study design. The study was conducted at 13 health centers in Lebong Regency consisting of 2 health center treatment units and 11 non-treatment health centers. Data collection was carried out by distributing questionnaires to all health centers, interviews, observations and document reviews. The collected data were analyzed descriptively by reviewing, tabulating data, combining research results to answer research questions and assessing their compliance with applicable laws and regulations. Solid B3 waste produced by health centers in Lebong Regency with the characteristics of infectious waste, sharp waste and pharmaceutical waste. The implementation of solid B3 waste management at health centers in Lebong Regency has not fully complied with the Minister of Environment and Forestry Regulation Number P.56/MenLHK-Setjen/2015. Since 2019, the largest solid B3 waste generated by health centers with treatment and non-treatment is sharps waste. Temporary storage facilities for B3 waste that have met the standards are Muara Aman health center, Talang Leak health center and Limau Pit health center. B3 waste management at health centers in Lebong Regency needs to be improved, especially in sorting, storage, provision of cold storage facilities, improvement of solid B3 waste management facilities, improvement of human resource capacity, improvement of SOP quality and budget planning.